The Role of Digital Human Resource Management Practices in Achieving Employee Well-being: An Analytical Study within the Civil Aviation Authority - misanjas misanjas; Ayman Kadhum Al-Qaraghouli; Ali Hasson Al-Taee; Ali Hasson Al-Taee ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The research aims to test the role of digital human resources management practices in achieving the well-being of workers in the Civil Aviation Authority, and to diagnose and explain the relationship between the research variables and their dimensions, and based on the basic problem by asking the extent of the impact of digital human resources management practices as an indicative variable represented by its four dimensions (learning and electronic development (Electronic performance evaluation, electronic reward and appreciation, electronic self-service for employees) in achieving employee well-being as a responding variable. Represented by its three dimensions (psychological well-being, workplace well-being, and life well-being), the data was collected into the research variables through a structured questionnaire specifically designed to look into the relationship between digital human resource management practices and employee well-being. The data were analyzed using different statistical methods, including descriptive analysis, correlation, and regression analysis. SPSS-26 software was used to process and extract the results. The study was conducted at the Civil Aviation Authority, focusing on evaluating discipline data to test the proposed speculations. Through the results, it was found that there is a significant impact of digital human resources management practices in achieving workers’ well-being, which indicates that digital human resources management practices play an active and influential role in enhancing workers’ well-being. Which indicates that digital HRM practices play an active and influential role in enhancing employee well-being. We therefore recommend expanding digital education programs to cover a variety of topics that are relevant to employees and aligned with their professional needs. In addition, Inspire employees to participate in multiple applications to enhance their diverse talent pools. This study uniquely explores the impact of digital HRM practices on the well-being of Civil Aviation Authority workers, providing insights into how digital HRM impacts workplace well-being.